Materializing Media Archaeologies: The MAD-P Hard Drive Excavation. (24th April 2015) - Perry, Sara; Morgan, Colleen
Abstract : Weaving together the theoretical and methodological assets of the fields of archaeology and media archaeology, this paper presents the first phase of the Media Archaeology Drive Project (MAD-P) wherein we aim to articulate a formal procedure for the excavation of media objects. Using an abandoned hard drive as our case study, we introduce our approach, discuss its varied intellectual implications, and suggest a series of next steps for developing the method and extending its deployment outwards to contemporary archaeologists as well as media archaeologists themselves.